2012
DOI: 10.1016/j.tim.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

GB virus C: the good boy virus?

Abstract: GB virus C (GBV-C) is a lymphotropic human virus discovered in 1995 that is related to hepatitis C virus (HCV). GBV-C infection has not been convincingly associated with any disease; however, several studies found an association between persistent GBV-C infection and improved survival in HIV-positive individuals. GBV-C infection modestly alters T cell homeostasis in vivo through various mechanisms, including modulation of chemokine and cytokine release and receptor expression, and by diminution of T cell activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
151
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(156 citation statements)
references
References 75 publications
(110 reference statements)
1
151
0
4
Order By: Relevance
“…In contrast, HPgV infection is considered non-pathogenic, although prevalence can exceed 40% in populations at high risk for exposure to blood-borne agents [2,3]. While controversial, several groups have also reported that co-infection of HPgV and human immunodeficiency virus (HIV) can delay progression to AIDS, presumably by decreasing HIV replication or perturbing the host immune response [3][4][5]. More recently, co-infection with HPgV in patients with Ebola virus disease has been reported to be associated with improved survival [6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HPgV infection is considered non-pathogenic, although prevalence can exceed 40% in populations at high risk for exposure to blood-borne agents [2,3]. While controversial, several groups have also reported that co-infection of HPgV and human immunodeficiency virus (HIV) can delay progression to AIDS, presumably by decreasing HIV replication or perturbing the host immune response [3][4][5]. More recently, co-infection with HPgV in patients with Ebola virus disease has been reported to be associated with improved survival [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, HIV-positive patients who also have GBV-C show slower disease progression. Several effects of GBV-C on HIV have been shown in clinical studies and in vitro, including downregulation of cell receptors for HIV entry, reduced replication of HIV, effects on interferon synthesis, and interactions with interleukin pathways (21).…”
mentioning
confidence: 99%
“…However, the impact of simian pegivirus infection on SIV pathogenesis in African monkeys has never been assessed, as pegiviruses in African monkeys have been described only recently. Given that HPgV infection attenuates HIV pathogenesis and improves mortality in HIV-infected humans (17)(18)(19)55), we examined the impact of SPgV ver coinfec- tion on cytokines influenced by SIV ver using a multivariate linear model. We did not find a significant difference in cytokine concentrations in SIV ver /SPgV ver -coinfected monkeys compared to SIV ver -monoinfected monkeys, nor did we find a difference in SIV loads between SPgV ver -positive and SPgV vernegative AGMs.…”
Section: Discussionmentioning
confidence: 99%
“…We consistently detected viruses from three genera: lentiviruses (i.e., SIV, Retroviridae family), pegiviruses (i.e., simian pegivirus [SPgV], Flaviviridae family), and simian arteriviruses (i.e., viruses distantly related to simian hemorrhagic fever virus [SHFV], Arteriviridae family). Viruses from these genera are relevant to NHP and human health: human pegivirus (HPgV) is associated with a reduction in pathological immune activation and mortality in HIV-infected people (17)(18)(19), while simian arteriviruses are prototypical preemergent zoonotic pathogens that have caused numerous outbreaks of viral hemorrhagic fever in captive Asianorigin macaque monkeys (20,21).…”
mentioning
confidence: 99%